1989
DOI: 10.1097/00000658-198910000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Benign Postoperative Biliary Strictures

Abstract: At The Johns Hopkins Hospital from 1979 through 1987, 42 patients had 45 procedures for benign postoperative biliary strictures. Three patients were managed with both surgery and balloon dilatation. Twenty-five patients underwent surgical repair with Roux-Y choledocho- or hepaticojejunostomy with postoperative transhepatic stenting for a mean of 13.8 +/- 1.3 months. Twenty patients had balloon dilatation a mean of 3.9 times and were stented transhepatically for a mean of 13.3 +/- 2.0 months. The two groups wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
2
10

Year Published

1992
1992
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(112 citation statements)
references
References 23 publications
3
97
2
10
Order By: Relevance
“…Pitt et al 32 established a 88% success rate after 4 years for postoperative benign stricture management in patients who did not undergo transplantation, which appears to be a better result compared with balloon dilatation. Kuo et al 30 reported a 89% success rate after 1 year, compared with 45% success rate for ERCP or PTC.…”
Section: Choice In Treatment Of Bsmentioning
confidence: 99%
“…Pitt et al 32 established a 88% success rate after 4 years for postoperative benign stricture management in patients who did not undergo transplantation, which appears to be a better result compared with balloon dilatation. Kuo et al 30 reported a 89% success rate after 1 year, compared with 45% success rate for ERCP or PTC.…”
Section: Choice In Treatment Of Bsmentioning
confidence: 99%
“…In general, it is recommended to maintain tubes for 3 to 6 months. In most complex cases, up to 12 months of stenting can be necessary [22,32,33]. The authors who use stents selectively consider that they are unnecessary if a tension-free anastomosis with wide stoma and good blood supply is accomplished.…”
Section: Figurementioning
confidence: 99%
“…The success rate and long term results of percutaneous treatment of benign strictures are reviewed and discussed in a number of articles 1,5,7,9,[11][12][13][14][15][16] . The percutaneous treatment of these strictures by dilatation has a success rate from 60 to 90 % 1 .…”
Section: Long-term Resultsmentioning
confidence: 99%